The relationships of eccentric strength and power with dynamic balance in male footballers - Booysen, M. J.; Gradidge, P. J.-G.; Watson, E. (Journal of Sports Sciences, 2015)
Unilateral balance is critical to kicking accuracy in football. In order to design interventions to improve dynamic balance, knowledge of the relationships between dynamic balance and specific neuromuscular factors such as eccentric strength and power is essential. Therefore, the aim was to determine the relationships of eccentric strength and power with dynamic balance in male footballers. The Y-balance test, eccentric isokinetic strength testing (knee extensors and flexors) and the countermovement jump were assessed in fifty male footballers (university (n = 27, mean age = 20.7 ± 1.84 years) and professional (n = 23, mean age = 23.0 ± 3.08 years). Spearman Rank Order correlations were used to determine the relationships of eccentric strength and power with dynamic balance. Multiple linear regression, adjusting for age, mass, stature, playing experience and competitive level was performed on significant relationships. Normalised reach score in the Y-balance test using the non-dominant leg for stance correlated with (1) eccentric strength of the non-dominant leg knee extensors in the university group (r = 0.50, P = 0.008) and (2) countermovement jump height in the university (r = 0.40, P = 0.04) and professional (r = 0.56, P = 0.006) football groups, respectively. No relationships were observed between eccentric strength (knee flexors) and normalised reach scores. Despite the addition of potential confounders, the relationship of power and dynamic balance was significant (r = 0.52, P < 0.0002). The ability to generate power correlates moderately with dynamic balance on the non-dominant leg in male footballers.